Protection of Children Personal Data in Digital Financial Services in Indonesia - Bernanda Gunawan, Aloysius (Journal of Law, Politic and Humanities, 2024)
This paper delves into the imperative factors for safeguarding children's personal data in digital banking services, highlighting the legal nuances and operational intricacies involved. As the banking sector increasingly integrates digital solutions, the protection of minors' data emerges as a critical concern, necessitating a thorough examination of the regulatory landscape and its practical implications. Focusing on Indonesia, the study scrutinizes national regulations on children's data protection within digital banking, juxtaposing these with international benchmarks, notably the General Data Protection Regulation (GDPR) framework adopted by European countries. This comparative analysis aims to unearth effective strategies and regulatory mechanisms that can fortify children's data privacy in the banking domain. Central to the discussion are the principles of consent, data minimization, and age verification, which are evaluated for their effectiveness in safeguarding young users' data. The paper assesses the technical and procedural measures that banks must implement to comply with these regulatory demands, ensuring the confidentiality and integrity of children's data. Challenges such as aligning technological advancements with stringent data protection standards are addressed, underscoring the pivotal role of various stakeholders, including regulatory bodies, banking institutions, and guardians, in cultivating a secure digital banking ecosystem for minors. Conclusively, the research proposes a set of recommendations aimed at refining Indonesia's legal framework regarding children's data protection in digital banking. By synthesizing insights from international practices, the study advocates for a holistic approach encompassing legislative reforms, technological enhancements, and educational initiatives to bolster the defenses around children's personal data in the digital financial landscape.